HABIT REVERSAL USED TO TREAT ONYCHOPHAGIA: A CASE REPORT - Georg Authried; Mathias Tiedemann Svendsen (Journal of Psychiatry Psychology and Behavioral Research, 2021)
Chronic nail biting (onychophagia) is a common habit which negatively impacts on the quality of life of those affected, has a negative social impact, and is accompanied with disabling inflammatory processes like gingivitis and paronychia. Habit reversal is a behaviour treatment procedure used to help patients get rid of the habit. The presented case report describes how a six-month period of habit reversal prescribed by the dermatologist was used to treat a 42-year male suffering from life-long onychophagia. During the treatment period, the patient experienced both an improved growth of nails and an improvement in quality of life, but never got fully cured from the habit. Finally, suggestions for an improved treatment success by prescribing habit reversal in specialized onychophagia clinics run by a multidisciplinary team (consisting of e.g., dermatologists, psychiatrists, and psychologists) who ensure regular follow-ups and patient compliance is provided.